Student attaintment of skill sets through capstone course in diploma in civil engineering programme/ Narita Noh, Nurul Izziyantie Mat Noor, Syed Muhammad Syed Yahya and Muhammad Bazli Faliq Mohd Puad - Noh, Narita; Mat Noor, Nurul Izziyantie; Syed Yahya, Syed Muhammad; Mohd Puad, Muhammad Bazli Faliq (UiTM Cawangan Johor, 2021)
Engineering education has become challenging compared to previous decade, the readiness of graduates before entering employement world is vital for the academician. Students are expected to possess all generic skill sets as needed by a qualified engineer including knowledge profile, engineering ability, communication, teamwork, and other relevant skills. In Malaysia, engineering graduates should possess 12 programme outcomes (PO) according to ETAC requirement, throughout the whole curriculum structure in diploma level. However, capstone course in Diploma Civil Engineering in UiTM only measures 3 main programme outcomes which are problem solving and scientific skills, communication skills, and ethics in engineering. The implementation of capstones course is reviewed for 3 consecutive semesters and student attaintment based on grade and programme outcomes is observed. This paper provides the assesment tools that had been mapped to programme outcomes through out 14 week lesson plan for final year students in Diploma Civil Engineering. This study 1 vas conducted in UiTM Pasir Gudang to measure the attainment of student '.s skill set based on programme outcomes stated in the syllabus. It shows that, a graduate is considered to be good in communication skills and ethics in engineering but average in problem solving skills and scientific skills. Thus, a few recomandations have been made to improve the skills attainment among students at the faculty level. Keywords: Civil Engineering, capstones course, student attainment